Towards a Non-Essentialist Pedagogy of “Islam” - Samman, Khaldoun (Teaching theology and religion, 2005)
Traversing a rock-strewn terrain of essentialist methodologies historically employed for teaching Islam, the author espouses a non-Essentialist pedagogy that combines critical reflection, analysis of historical methods, and development of an appreciation for alternative notions about Islam and global interdependence. In this essay the author contends that teaching Islam ought to avoid our and their language and instead aim at helping students think in critically reflective, creative, and relational ways so that they might learn to “think of civilizations as transformative, reflexive, and fluid entities.”